Muscle functional MRI analysis of trunk muscle recruitment during extension exercises in asymptomatic individuals - De Ridder, E. M. D.; Van Oosterwijck, J. O.; Vleeming, A.; Vanderstraeten, G. G.; Danneels, L. A. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The present study examined the activity levels of the thoracic and lumbar extensor muscles during different extension exercise modalities in healthy individuals. Therefore, 14 subjects performed four different types of extension exercises in prone position: dynamic trunk extension, dynamic-static trunk extension, dynamic leg extension, and dynamic-static leg extension. Pre- and post-exercise muscle functional magnetic resonance imaging scans from the latissimus dorsi, the thoracic and lumbar parts of the longissimus, iliocostalis, and multifidus were performed. Differences in water relaxation values (T2-relaxation) before and after exercise were calculated (T2-shift) as a measure of muscle activity and compared between extension modalities. Linear mixed-model analysis revealed higher lumbar extensor activity during trunk extension compared with leg extension (T2-shift of 5.01 ms and 3.55 ms, respectively) and during the dynamic-static exercise performance compared with the dynamic exercise performance (T2-shift of 4.77 ms and 3.55 ms, respectively). No significant differences in the thoracic extensor activity between the exercises could be demonstrated. During all extension exercises, the latissimus dorsi was the least activated compared with the paraspinal muscles. While all extension exercises are equivalent effective to train the thoracic muscles, trunk extension exercises performed in a dynamic-static way are the most appropriate to enhance lumbar muscle strength.